MODEL PENTAHELIX DALAM PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDES): STUDI PADA BUMDES PANGGUNG LESTARI - Hakim, Husnul; Yusuf Wahyudi, Eko (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
In the midst of the confusion and difficulties experienced by the average village in Indonesia in realizing a Badan Usaha Milik Desa (BUMDes), Panggung Lestari was named as a national pilot BUMDes. This BUMDes has successfully supported Panggungharjo Village to become an economically independent village and provided solutions to socio-economic problems faced by the villagers. Using a qualitative-descriptive method, this research aims to explore the extent of Panggung Lestari’s development when viewed within the pentahelix model, which is a collaboration model involving five main actors: academics, business entities, communities, government, and media. The results show that among these five sectors, the sector that has the most central role is the Panggungharjo Village Government, which is not only a legitimator, but also an initiator, organizer, as well as a control agent. The next central sector is the village community that actively participates in both channeling aspirations and managing BUMDes. The academic sector supports product research and fosters project development. The business entity is a sector that contributes to the assessment system, becomes a marketing collaborator, and also a product developer collaborator. The media sector raises the prestige of Panggung Lestari as a modern BUMDes in the form of “practice 4.0”.